Visualization and Classification of Deeply Seated Collateral Networks in Moyamoya Angiopathy with 7T MRI - Matsushige, T. (AJNR Am J Neuroradiol, 2018)
BACKGROUND AND PURPOSE: Collateral networks in Moyamoya angiopathy have a complex angioarchitecture difficult to comprehend on conventional examinations. This study aimed to evaluate morphologic patterns and the delineation of deeply seated collateral networks using ultra-high-field MRA in comparison with conventional DSA. MATERIALS AND METHODS: Fifteen white patients with Moyamoya angiopathy were investigated in this prospective trial. Sequences acquired at 7T were TOF-MRA with 0.22 × 0.22 × 0.41 mm(3) resolution and MPRAGE with 0.7 × 0.7 × 0.7 mm(3) resolution. Four raters evaluated the presence of deeply seated collateral networks and image quality in a consensus reading of DSA, TOF-MRA, and MPRAGE using a 5-point scale in axial source images and maximum intensity projections. Delineation of deeply seated collateral networks by different imaging modalities was compared by means of the McNemar test, whereas image quality was compared using the Wilcoxon signed-rank test. RESULTS: The relevant deeply seated collateral networks were classified into 2 categories and 6 pathways. A total of 100 collateral networks were detected on DSA; 106, on TOF-MRA; and 73, on MPRAGE. Delineation of deeply seated collateral networks was comparable between TOF-MRA and DSA (P = .25); however, both were better than MPRAGE (P < .001). CONCLUSIONS: This study demonstrates excellent delineation of 6 distinct deeply seated collateral network pathways in Moyamoya angiopathy in white adults using 7T TOF-MRA, comparable to DSA.